(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
One of the globalization results is (VAT) , so it is important to consider its results and impact on the tax system. The Iraqi economy having wittnisd an acute transition period , still in need for a better care in aim to back it, especialy from the tax system. The research is concerned with the (VAT) and its details –And for five chapters all the problomes connect are displayed .But yet the new system does not comply with the modern development and this is one of the defects of (VAT) in Iraq. The history of (VAT)was also studied mentiorned and studied. As a conclusion (VAT) is one of the most important taxes imposed on production, sales , and consumptions . As a recommendation a reform is very important in the tax system .